Invertebrate miRNA pva-small RNA-11881/pva-miR-11881 as a potential RNA-based therapeutic against white spot syndrome virus in infected shrimp - Pun Sangchai; Peter Sarnow; Kunlaya Somboonwiwat (Proceedings of the National Academy of Sciences, 2026)
Small RNAs and microRNAs (miRNAs) play diverse roles in host virus interactions and hold promise for therapeutic applications. An uncharacterized shrimp miRNA with potent activity against white spot syndrome virus (WSSV), a major double-stranded DNA pathogen in aquaculture, was identified and characterized. Among the 1,239 differentially expressed unannotated small RNAs in Penaeus vannamei hemocytes, one of the most strongly downregulated candidates, termed pva-small RNA-11881 or pva-miR-11881, was predicted to target multiple WSSV genes. A pva-small RNA-11881/pva-miR-11881 isomir that originates from the 5′ untranslated region of a host lipase 3-like gene was identified. Its primary transcript contains Drosha and Dicer processing sites, and the precursor exhibits canonical pre-miRNA features. In vivo administration of its primary transcript, pva-pri-miR-11881, significantly reduced WSSV copy number and improved shrimp survival. Mechanistically, pva-miR-11881 directly suppresses crucial WSSV genes WSSV004 , WSSV164 , and WSSV419 and modulates the host immune response against WSSV infection by enhancing phenoloxidase activity, thereby reducing apoptosis and necrosis, and promoting caspase-1-mediated cell death. These findings reveal that the pva-miR-11881 in P. vannamei holds strong potential as a biotherapeutic agent for managing viral diseases in shrimp.